2013
DOI: 10.1063/1.4852615
|View full text |Cite
|
Sign up to set email alerts
|

Doping mechanisms in graphene-MoS2 hybrids

Abstract: We present a joint theoretical and experimental investigation of charge doping and electronic potential landscapes in hybrid structures composed of graphene and semiconducting single layer MoS2. From first-principles simulations we find electron doping of graphene due to the presence of rhenium impurities in MoS2. Furthermore, we show that MoS2 edges give rise to charge reordering and a potential shift in graphene, which can be controlled through external gate voltages. The interplay of edge and impurity effec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
97
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 23 publications
6
97
1
Order By: Relevance
“…Another arrangement, where a C atom sits above a S atom, has been shown to be energetically and electronically equivalent to that of the TM configuration. 34,35 Once the graphene/MoS 2 supercell is constructed, oxygen functional groups are randomly attached above and below the graphene plane. 38,39 GO structures are obtained by relaxing the supercell without the MoS 2 monolayer first, and then the MoS 2 monolayer is introduced with an initial distance between the C plane of GO and the Mo plane of MoS 2 of 4.85 Å, which is the van der Waals distance obtained for the MoS 2 /graphene case.…”
mentioning
confidence: 99%
“…Another arrangement, where a C atom sits above a S atom, has been shown to be energetically and electronically equivalent to that of the TM configuration. 34,35 Once the graphene/MoS 2 supercell is constructed, oxygen functional groups are randomly attached above and below the graphene plane. 38,39 GO structures are obtained by relaxing the supercell without the MoS 2 monolayer first, and then the MoS 2 monolayer is introduced with an initial distance between the C plane of GO and the Mo plane of MoS 2 of 4.85 Å, which is the van der Waals distance obtained for the MoS 2 /graphene case.…”
mentioning
confidence: 99%
“…14 Hence, the study of the interfaces between MoS 2 and graphene (or graphite) is critically important and may provide useful hints for various applications. 6,15 Shi et al have recently reported the formation of MoS 2 flakes on the graphene surface via thermal decomposition of ammonium thiomolybdate. 16 Although there is a large lattice mismatch between the MoS 2 and the graphene structure, graphene can serve as an epitaxial substrate for MoS 2 .…”
mentioning
confidence: 99%
“…Recently, many proposed novel devices are based on heterostructures of MoS 2 and graphene. [5][6][7][8][9] Such heterostructures offer the possibility to create devices with new functionalities or better performance in electronic logic and memory devices, [9][10][11] and also offer great potential in the hydrogen evolution reaction. 12 Graphene/MoS 2 heterostructures have also been adopted to demonstrate an extremely high photosensitivity and gain 13 as well as the ultrasensitive detection of DNA hybridization.…”
mentioning
confidence: 99%
“…Previously, several approaches have been undertaken to alter the solid-state properties of MoS 2 , including chemical doping 3,[10][11][12] , intercalation 13,14 , surface functionalization 15 and defect engineering 11,16,17 . Furthermore, previous theoretical studies have suggested that an iso-structural semiconducting to metallic (S-M) transition in multilayered MoS 2 can be induced by pressure or strain [18][19][20] .…”
mentioning
confidence: 99%